Performance enhancement of flat-plate and parabolic trough solar collector using nanofluid for water heating application - Mostafa AbdEl-Rady Abu-Zeid; Yasser Elhenawy; Mohamed Bassyouni; Thokozani Majozi; Monica Toderas; O.A. Al-Qabandi; Sameh Said Kishk (Results in Engineering, 2024)
Flat plate solar collector (FPSC) and parabolic trough solar collector (PTSC) are widely used for residential solar water heating (SWH) applications. This work studied two different solar collector systems. Nanofluid and its influence on the residential solar water heating (SWH) systems were investigated. The two SWH systems were designed, installed, tested, and compared at varying mass flow rates (mf) of 0.47, 1.05, and 1.75 kg min−1 in ambient environmental conditions. The comparative study was conducted according to thermal efficiency (ηth), useful energy gain (QU), stored energy (QS), outlet hot water temperature (To), and difference temperature (ΔT) between the cold inlet and hot outlet water from the collectors. The analysis of outcomes showed that the PTSC was more efficient than FPSC. The FPSC and PTSC systems performance were investigated using two different types of nanofluids. Carbon nanotubes in water and ethylene glycol were utilized. A remarkable improvement in the average thermal efficiency 64.1 % and 80.6 % of FPSC and PTSC systems using ethylene glycol nanofluid were obtained respectively. The total reduction in CO2 emissions was 31.26 kg/day and 39.28 kg/day for the FPSCs and PTSCs, respectively in the presence of ethylene glycol nanofluid. A significant saving in CO2 release is owing to the renewable clean energy of solar collectors.